Evaluation of drug prevention programmes and development of a drug-free school framework - Durrah Athirah Walid (2023)
The purpose of this study was to identify existing drug prevention education programs in schools, evaluate the effectiveness of drug prevention education programs in schools, and build a drug-free school framework. There are two research methods used to obtain data in this study. The first research design used mixed methods involving qualitative and quantitative data collection. The second design is a design and development research method that has three main phases including the needs analysis phase, the design and development phase, and the evaluation phase. The respondents selected in identifying and evaluating this drug prevention education program are a total of 190 school students, 40 drug prevention education teachers, school counselors, and school administrators, while 10 counseling experts and practitioners have been involved in building the drug-free school framework. The data shows that the most activities carried out in schools are drug education in the integrated high school curriculum (91.3%), while the least carried out activities are the Student Intervention Program (15.2%). Data showed that students responded positively at all levels of assessment, including reaction levels, learning outcomes, behaviors, and program outcomes. However, in terms of implementing drug prevention education programs, there are suggestions for improvements needed to conduct drug prevention education effectively in schools. Further findings is a proposal for the drug-free school framework by using fuzzy dephi techniques that include elements such as low-risk aspects and high protective factors, learning outcomes, training, and support, information availability, research-based psycho-educational programs, team development, interactive engagement, group appropriateness, suitability to targeted student group, realizing a climate of education, social collaboration, monitoring progress and outcomes, and finally policies and procedures. The implications of the study can be used in the field of academics and counseling to prevent drug abuse among students more effectively